Phasa Thai Swear Words Used By Thai People - Sutrini, Ayu Nyoman; Budasi, I Gede; Ramendra, Dewa Putu (IJLHE: International Journal of Language, Humanities, and Education, 2025)
This study aims to analyze the Phasa Thai swear words used by Thai people, which focus on their forms, references, and functions. A descriptive qualitative method was employed, along with the data collection method, which included document analysis, a questionnaire, and an interview. The researcher serves as the primary instrument. Data were collected through document analysis, questionnaires, and interviews, and then evaluated using Miles and Huberman's theory. The study's subjects included three informants chosen along with the specific criteria. The results revealed that there are twenty-seven (27) Phasa Thai swear words, in the form of words categorized into monomorphemic (11) and polymorphemic words (15), as well as phrases (6). The study identified nine (9) primary references where there are two (2) new references emerged from this study. The functions of these swear words include expressing emotion, insulting someone, joking, and provoking. This research contributes to understanding the role of offensive language in Phasa Thai and its social functions. Which is appropriate for cross-cultural understanding.